CARBOHYDRATE COMPLEX OF THE AERIAL PARTS OF ARTEMISIA JUNCEA (International Scientific Journal Alfraganus, 2025)
The carbohydrate complex of the aerial parts of Artemisia Juncea was studied. The complex was isolated, its physicochemical parameters were determined, the monosaccharide composition was established, and IR spectra were analyzed. Water-soluble polysaccharides were identified and shown to be heterogeneous in nature. The presence of highly esterified pectin substances and hemicellulose was also confirmed.
Keywords: polysaccharides; water-soluble polysaccharide; pectin sub